Evaluation of Hearing Function by Auditory Brainstem Response in Newborn Patients with Hydrocephalus before and after Ventriculoperitoneal Shunt Surgery - Ozturk, Sait; Erol, Fatih Serhat; Akgun, Bekir; Kaplan, Metin; Birkent, Omer Faruk; Karlidag, Turgut (Karger, 2016)
Background/Aim: There is currently no objective evaluation of hearing in patients with hydrocephalus (HCP), and we could not find any study in the literature comprising a sufficient number of patients with a high level of scientific evidence. In the current study, we used the auditory brainstem response (ABR) test to assess whether hearing function in patients with HCP is altered after ventriculoperitoneal shunt surgery. Methods: In total, 20 newborn patients with HCP (13 female, 7 male) were enrolled in this study. For each patient, ABR testing was performed at three time points: 1 day prior to the operation and on days 7 and 90 after the operation. ABRs using click stimuli of 90, 70, 50 and 30 dB nHL (normal hearing level) were achieved for V-wave latency, and I-III and I-IV interpeak latencies for both ears were recorded. Variance analysis for parametric data and Tukey's post hoc honest significant difference test were used to demonstrate the relationship between the results obtained from the different recording periods. Results were considered significant at p < 0.05, and 95% confidence intervals were calculated. Results: The mean values of the ABR tests were compared between the pre- and postoperative results, which showed an increase (faster transmission) of nerve conduction velocity of 0.2 ms. The results were not statistically significant for 50 and 90 dB (p > 0.05) but were significant for 30 and 70 dB (p < 0.05). Conclusion: Diagnosis in hydrocephalic patients is important not only for the treatment but also for the prevention of HCP-associated complications. Early treatment appears to be promising in terms of auditory benefit. Prompt diagnosis and treatment are therefore essential as soon as possible. (C) 2016 S. Karger AG, Basel
Keywords: Auditory brainstem response; Hearing loss; Hydrocephalus; Ventriculoperitoneal shunt